Localization of the C terminus of the assembly domain of hepatitis B virus capsid protein: Implications for morphogenesis and organization of encapsidated RNA - Zlotnick, A. (National Academy of Sciences, 1997)
The capsid protein of hepatitis B virus, consisting of an “assembly” domain (residues 1–149) and an RNA-binding “protamine” domain (residues 150–183), assembles from dimers into icosahedral capsids of two different sizes. The C terminus of the assembly domain (residues 140–149) functions as a morphogenetic switch, longer C termini favoring a higher proportion of the larger capsids, it also connects the protamine domain to the capsid shell. We now have defined the location of this peptide in capsids assembled in vitro by engineering a mutant assembly domain with a single cysteine at its C terminus (residue 150), labeling it with a gold cluster and visualizing the cluster by cryo-electron microscopy. The labeled protein is unimpaired in its ability to form capsids. Our density map reveals a single undecagold cluster under each fivefold and quasi-sixfold vertex, connected to sites at either end of the undersides of the dimers. Considering the geometry of the vertices, the C termini must be more crowded at the fivefolds. Thus, a bulky C terminus would be expected to favor formation of the larger (T = 4) capsids, which have a greater proportion of quasi-sixfolds. Capsids assembled by expressing the full-length protein in Escherichia coli package bacterial RNAs in amounts equivalent to the viral pregenome. Our density map of these capsids reveals a distinct inner shell of density—the RNA. The RNA is connected to the protein shell via the C-terminal linkers and also makes contact around the dimer axes.